Identification of Hub Genes and Key Pathways Associated With Bipolar Disorder Based on Weighted Gene Co-expression Network Analysis - Liu, Yang; Gu, Hui-Yun; Zhu, Jie; Niu, Yu-Ming; Zhang, Chao; Guo, Guang-Ling (Frontiers in Physiology, 2019)
Bipolar disorder (BD) is a complex mental disorder with high mortality and disability rates worldwide; however, research on its pathogenesis and diagnostic methods remains limited. This study aimed to elucidate potential candidate hub genes and key pathways related to BD in a pre-frontal cortex sample. Raw gene expression profile files of GSE53987, including thirty-six samples, were obtained from the Gene Expression Omnibus database. After data pre-processing, 10,094 genes were selected for weighted gene co-expression network analysis (WGCNA). After dividing highly related genes into 19 modules, we found that the pink, midnight blue, and brown modules were highly correlated with BD. Functional annotation and pathway enrichment analysis of modules were conducted through the Enrichr database. The enrichment analysis results indicated some key pathways. One of the most remarkable significant pathways is the Hippo signaling pathway and its positive transcriptional regulation. Finally, we found 30 hub genes in three modules. We found that hub genes with a high degree of connectivity in the PPI network are significantly enriched in positive regulation of transcription. In addition, the hub genes were validated by another dataset (GSE12649). Taken together, the identification of these hub genes and enrichment pathways may have important clinical implications for BD treatment and diagnosis.